Conformation and Physical Structure of Tropoelastin from Human Vascular Cells: Influence of Cells Lipid Loading. (12th May 2014) - Samouillan, Valerie; Dandurand, Jany; Nasarre, Laura; Badimon, Lina; Lacabanne, Colette; Llorente-Cortés, Vicenta
Abstract : Aggregated low density lipoproteins (agLDL) contribute to massive intracellular cholesteryl ester (CE) accumulation in human vascular smooth muscle cells (VSMC). Our aim was to determine the conformational and physical structure of agLDL and elastic material produced either by control human VSMC or by agLDL-loaded human VSMC (agLDL-VSMC). At the conformational level scanned by FTIR spectroscopy, a new undefined, probably non-H-bonded, structure for tropoelastin produced by agLDL-VSMC is revealed. By differential scanning calorimetry, a decrease of water affinity and a drop of the glass transition associated with aggregated tropoelastin (from 200°C to 159°C) in the supernatant from agLDL VSMC are evidenced. This second phenomenon is due to an interaction between agLDL and tropoelastin as detected by the weak specific FTIR absorption band of agLDL in supernatant from agLDL-loaded VSMC.